The organization issue of students’ individual educational and research activities (Pedagogy of Higher and Secondary Education, 2016)
Sobolyeva S. M. The organization issue of students’ individual educational and research activities.The role of individual work of students, including individual research tasks, in training high-qualified specialists and forming quality of education is considered in the article. The essence of the concept of individual educational and research tasks as a form of extracurricular individual work of student, which has educational, research or design nature, has been used in the educational course and based on the searching and analyzing of certain parts of the discipline material, its systematization, synthesis. Attention is paid to the peculiarities of educational and research activity of student in higher education as a form of creative work.The quality of students’ individual research tasks has been analyzed. The results of pedagogical research have identified the main causes of low quality tasks, such as insufficient basic knowledge of subjects school course, academic procrastination, low information culture of students and lack of academic motivation. Special attenion is paid to the necessity of development of personal, motivational, psychological, pedagogical, didactic, information technology, technical and ergonomic conditions during students’ research activity.Basic structural components of educational and research activity of students (including motivational, targeted, management, control, evaluation and analytical) have been determined in the article. It is noted that the effectiveness of students’ research activity depends on the quality of teacher managing and using elements of pedagogical coaching during consultations. Coaching technology is interpreted as a developmental counseling that promotes development of the necessary and new skills, helps to find reserves and ways to solve certain problems by yourself. According to results, the most effective form of implementation individual educational and research tasks in the disciplines of social and humanities are research projects that involve conducting empirical research.The prospects for further research are on improving information and methodological support of educational and research activity of students, finding the most effective forms of implementation and protection of individual educational and research tasks.
Keywords: individual student’s work; individual educational and research activities; individual research task; project; project activities; coaching; pedagogical coaching; coaching technology